2006
DOI: 10.1007/s00414-006-0113-y
|View full text |Cite
|
Sign up to set email alerts
|

Two universal primer sets for species identification among vertebrates

Abstract: The aim of this study was to develop a simple method using universal primers for species identification based on direct PCR sequencing. Two primer sets were designed based on the conserved regions of the 12S and 16S rRNA loci detected by the comprehensive sequence comparison among 30 mammalian whole mitochondrial genomes. In humans, the expected sizes of PCR products of the 12S and 16S rRNAs were 215 and 244 bp, respectively. Both primer sets successfully amplified the expected PCR products from various kinds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
163
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(164 citation statements)
references
References 16 publications
1
163
0
Order By: Relevance
“…Of those, 88 blood samples were from eleven species of wild animals including Rattus tiomanicus (R. tiomanicus) (19), Rattus tanezumi (R. tanezumi) (25), Rattus rajah (R. rajah) (4), Leopoldamys sabanus (L. sabanus) (7), Niviventor cremoriventor (N. cremoriventor) (2), Sundamys muelleri (S. muelleri) (8), Tupaia glis (T. glis) (16), Rhinosciurus laticaudatus (R. laticaudatus) (2), Callosciurus spp. (1), Maxomys whiteheadi (M. whiteheadi) (3), Trpaia minor (T. minor) (1).…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 88 blood samples were from eleven species of wild animals including Rattus tiomanicus (R. tiomanicus) (19), Rattus tanezumi (R. tanezumi) (25), Rattus rajah (R. rajah) (4), Leopoldamys sabanus (L. sabanus) (7), Niviventor cremoriventor (N. cremoriventor) (2), Sundamys muelleri (S. muelleri) (8), Tupaia glis (T. glis) (16), Rhinosciurus laticaudatus (R. laticaudatus) (2), Callosciurus spp. (1), Maxomys whiteheadi (M. whiteheadi) (3), Trpaia minor (T. minor) (1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proved that the regions residing in the 12S and 16S rRNA loci in the mitochondrial genome among mammals are more strictly conserved than the region in the cytochrome b locus (Kitano et al 2007;Palumbi 1996). These regions are located in both loop and stem portions in the secondary structure.…”
Section: Resultsmentioning
confidence: 99%
“…As stated by Kitano et al (2007) direct sequencing of the PCR products allowed comparative analysis of the unknown DNA sequences and those already deposited in the databases by using the BLAST program. This study showed, though some fish species were from the same genus, the analysis of phylogenetic tree showed that they are genetically distant from each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some existing universal primers of 12S mitochondrial rRNA have been used to effectively amplify 12S mitochondrial rRNA from mammals and some vertebrates effectively (Springer et al, 1995;Wang et al, 2000;Kitano et al, 2007), the amplification scope of these existent primers is relatively limited in marine fishes because of the differences in the used template gene that was used to design the universal primers. Therefore, a pair of universal 12S mitochondrial rRNA gene primers was designed based on the gene sequences of different kinds of marine fishes.…”
Section: XX Jin Et Almentioning
confidence: 99%